Basic Signs of the Concepts of Bogatstvo and Wealth in Russian and English Language Pictures of the World - M. M. Mendesheva (Вестник Кемеровского государственного университета, 2022)
The article compares the motivating signs of the concepts of bogatstvo and wealth based on eleven Russian etymological dictionaries and seven English etymological and four explanatory dictionaries. The author analyzed the words bogatstvo and wealth as the main representatives of the concepts in question and identified their motivating signs. The interpretation relied on the theory of mentality. The Russian concept of bogatstvo appeared to have 15 motivating sings that could be grouped into five blocks: 1) material wealth, 2) allocation of resources, 3) a share of property, 4) spiritual wealth, 5) values. The English concept of wealth demonstrated fourteen motivating signs represented as three blocks: 1) material wealth, 2) values, 3) spiritual wealth.